Pengadaan Taman Bermain Sebagai Upaya MengurangiKecanduan Smartphone pada Siswa-Siswi TK dan SD di Desa Wonokoyo Kabupaten Situbondo - Agus Mahar Mahardiyanto (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2023)
PROVIDING A PLAYGROUND AS AN EFFORT TO REDUCE SMARTPHONE ADDICTION AMONG KINDERGARTENAND ELEMENTARY SCHOOL STUDENTS IN WONOKOYO VILLAGE, SITUBONDO REGENCY. Playground is a means oflearning and playing for children in the digital era. The problem identified in the Wonokoyo Village community is the widespread use ofsmartphones among children. Children in Wonokoyo Village always play online games and forget about other mandatory activities.Therefore, we UNEJ UMD KKN students in a group of 150 held a playground and a reading corner with the aim of reducing the use ofsmartphones in children. The target of the playground is early childhood, kindergarten and elementary school students in WonokoyoVillage, Kapongan District, Situbondo Regency. The implementation of this work program begins with playing together and introducingtraditional games. In addition, we also provide education about cleanliness and moral education. The result of this work program activityis the establishment of a Playground which is placed at the Dahlia Wonokoyo Early Childhood School so that it can reduce the level ofsmartphone use in children.